DEVELOPMENT OF THE USE OF EDUCATIONAL TECHNOLOGY BASED ON THE QUIZIZZ APPLICATION IN INCREASING STUDENTS' INTEREST IN LEARNING AT SMK NEGERI 1 SITOLU ORI - Gea, Dedi Septinius; Harefa, Trisman; Harefa, Afore Tahir; Riswan Zega (Esteem Journal of English Education Study Programme, 2025)
The purpose of this study is to increase student interest in learning at SMK Negeri 1 Sitolu Ori by developing strategies for using the Quizizz application, developing the use of the Quizizz program, and determining how students react to its use. The need to identify practical methods for raising student enthusiasm and engagement in a classroom setting is the main emphasis of this study. This study uses Quizizz, which provides interactive tests and gamification features, to evaluate how it affects student engagement and interest. Surveys were used to collect data both before and after implementation. According to the findings, using Quizizz greatly raised students' motivation and involvement in their education. This study employed a 4D development model in conjunction with a Research and Development (R&D) methodology. The validation questionnaire validated the results, which demonstrated that the Quizizz application used in this study was highly practical and viable. With a 90% agreement level, media professionals assigned an average score of 0.9, placing it in the extremely possible category. With an agreement level of 81.66%, material experts assigned an average score of 0.81, placing them in the extremely feasible category. With a 100% agreement level, practitioner experts assigned an average score of 1, placing it in the extremely possible category.  Based on these findings, the study comes to the conclusion that using Quizizz as an educational technology tool to increase students' interest in studying at SMK Negeri 1 Sitolu Ori has been shown to be both practicable and useful. Teachers and other educators are advised to learn how to use the Quizizz app for various learning activities.